A novel low-noise fully differential CMOS instrumentation amplifier with 1.88 noise efficiency factor for biomedical and sensor applications. (July 2016) - Das, Devarshi Mrinal; Srivastava, Abhishek; Ananthapadmanabhan, J.; Ahmad, Meraj; Baghini, Maryam Shojaei
Abstract: In this paper, we present a novel instrumentation amplifier (INA) topology for mobile bio-medical data acquisition platforms. The proposed INA features a PMOS-NMOS complimentary transistor input pair biased in sub-threshold region to effectively boost the transconductance of the input pair and reduce the input referred noise. There are two embedded common-mode feedback circuits which help to establish the common-mode voltages without consuming extra power. One is at the output of the first stage (i.e. at the drain connection of the complimentary transistors) and the other at the final output stage. The INA provides a measured gain of 40 dB and a bandwidth of 11 kHz. The measured integrated noise is 0.78 μ V rms (50 mHz to 11 kHz) with measured CMRR of greater than 100 dB. The proposed amplifier is versatile and hence capable of conditioning various bio-potential signals like Electrocardiogram (ECG), Electroencephalogram (EEG), Electromyogram (EMG) and Electrooculogram (EOG) as well as signals produced from sensors. A prototype chip has been fabricated in UMC 180 nm mixed-mode CMOS technology operating at 1.8 V power supply and occupying an area of 415 × 230 μ m 2 . The simulation and experimentally measured results are presented in this paper. NEF (noise efficiency factor) of 1.88 is obtained from measurement results. Hence the amplifier features for the first time a very low NEF (1.88) and high CMRR ( > 100 dB ). A compact ExG conditioning and acquisition system has been developed and used to measure ECG, EEG, EMG and EOG signals from human subjects by deploying the proposed INA.